The effect of maturity and extraction solvents on bioactive compounds and antioxidant activity of mulberry (morus alba) fruits and leaves - Centhyea; Ruzaidi Azli Mohd Mokhtar; Muhamad Shirwan Abdullah Sani; Nor Qhairul Izzreen Mohd Noor (2022)
Cultivation location, maturity levels, and extraction solvents could affect the bioactive compounds and biological activities of mulberry (Morus alba Linnaeus). The lack of study on Malaysia-grown mulberry causes its underutilization. This study investigated the total bioactive compounds content and the antioxidant activity of Sabah-grown mulberry fruits and leaves. Samples were analyzed at two different maturity stages (fruits: red mature and black fully ripe; leaves: mature and young) and extracted using 70% (v/v) methanol, 60% (v/v) ethanol and 65% (v/v) acetone. The analyses included the total content of phenolic, flavonoid, and anthocyanin, UHPLC-DAD quantification of chlorogenic acid and rutin, Free Radical Scavenging 2.2-Dyphenyl-1-Pikrilhidrazil (DPPH), Radical Cation 2,2’-Azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) and Ferric Reduction Antioxidant Power (FRAP) assays. Results showed that mulberry fruits demonstrated maturity-dependent increment (except UHPLC-DAD quantification), while the leaves revealed maturity-dependent reduction. Principal component analysis (PCA) displayed 65% (v/v) acetone black fully ripe fruits in 65% (v/v) acetone as the best phenolics and antioxidant sources. However, the 60% (v/v) ethanol black fully ripe fruits contained 20.08%–68.43% higher total anthocyanins. Meanwhile, the 65% (v/v) acetone and 70% (v/v) methanol red mature fruits were higher in chlorogenic acid (27.53%–47.12%) and rutin (31.42%–35.92%) than other fruit extracts, respectively. For leaves, young leaves in 65% (v/v) acetone young leaves were the best phenolics and antioxidant sources. However, the 60% (v/v) ethanol young leaves possessed greater chlorogenic acid (19.56%–74.11%) than other leaf extracts. Overall, Malaysia-grown mulberry is rich in phenolics and antioxidants, suggesting its potential application in food and pharmaceutical products.